2007
DOI: 10.1007/s10695-007-9148-3
|View full text |Cite
|
Sign up to set email alerts
|

Determination of spermatological properties of male Liza abu (Heckel, 1843) in Atatürk Dam Lake, Şanlıurfa

Abstract: The aim of this study was to determine the spermatological characteristics in male L. abu during the spawning season. Semen was collected weekly by abdominal massage from 26 males in March. In collected semen, volume, motility, duration of motility, concentration and pH were determined. In the L. abu sperm, volume (microl), motility (%), duration of motility (s), concentration (x10(9)/ml), and pH values were found 45.76 +/- 3.55, 54.25 +/- 2.93, 330.15 +/- 37.92, 4.27 +/- 0.40 and 7.87 +/- 0.05, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 25 publications
1
5
0
Order By: Relevance
“…Similar results have been found for other carp species (Khanam, Nahiduzzaman, Hassan, Sultana, Rafiquzzaman & Hossain 2008;Verma et al 2009). Seminal plasma pH of L. calbasu was slightly alkaline and is similar to other teleosts, including Puntius sarana (Khanam et al 2008), Liza abu (Sahinoz, Aral & Dogu 2008) and Ctenopharyngodon idella (Bozkurt, Ogretmen, Ercin & Yildiz 2008).…”
Section: Spermatological Parameterssupporting
confidence: 65%
See 1 more Smart Citation
“…Similar results have been found for other carp species (Khanam, Nahiduzzaman, Hassan, Sultana, Rafiquzzaman & Hossain 2008;Verma et al 2009). Seminal plasma pH of L. calbasu was slightly alkaline and is similar to other teleosts, including Puntius sarana (Khanam et al 2008), Liza abu (Sahinoz, Aral & Dogu 2008) and Ctenopharyngodon idella (Bozkurt, Ogretmen, Ercin & Yildiz 2008).…”
Section: Spermatological Parameterssupporting
confidence: 65%
“…Seminal plasma pH of L. calbasu was slightly alkaline and is similar to other teleosts, including Puntius sarana (Khanam et al . ), Liza abu (Sahinoz, Aral & Dogu ) and Ctenopharyngodon idella (Bozkurt, Ogretmen, Ercin & Yildiz ).…”
Section: Discussionmentioning
confidence: 99%
“…Seminal plasma pH may affect final maturation of spermatozoa. Also, duration of sperm motility in males could be influenced by the changes of semen pH (Sahinoz et al, 2008). In cyprinids, it has been shown that extracellular and intracellular pH as well as the ionic composition of the seminal plasma influence the initiation and duration of sperm motility (Marian et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Deviations from 1:1 null hypothesis were statistically tested using the chi-square analysis ( 2 -test) (Av ar, 1995). The von Bertalanffy growth equations were used to describe growth of the species (Sparre and Venema, 1992):…”
Section: Methodsmentioning
confidence: 99%
“…It is a target of a commercial fishery because of high economic importance (Abd et al, 2009). Despite intensive investigations of the growth, reproduction and ecology of abu mullet in the Tigris and Euphrates Rivers (Al-Nasırı and Sirajul, 1978;Al-Yamour et al, 1988;Ünlü et al, 2000;ahinöz et al, 2008;Chelemal et al, 2009;Kaya, 2010;ahinöz et al, 2010) and other places in the Arabian Gulf and marshes (Nasır and Naama, 1988;Naama and Muhsen, 1986), information on growth, age and reproduction of abu mullet in the Orontes River is still not available. The aim of this study is to provide information on the biological aspects of abu mullet inhabiting the Orontes River basin.…”
Section: Introductionmentioning
confidence: 99%